Risk Behavior of Onion Farmers in the District Enrekang - Nurhapsa Nurhapsa; Arham Arham; Sitti Nurani Sirajuddin (Sebelas Maret Business Review, 2018)
This study aimed to analyze the risk behavior of onion farmers in District Enrekang. A random sample of 75 onion farmers was selected for interviews. The model used to analyze the behavior of risk is a model developed by Kumbhakar (2002). The analysis showed that the average behavior of onion farmers are risk averse to the use of various inputs. In order for farmers to take risks and enhance productivity, strengthening institutions such as farmers' groups or unions as well as enhancing the role of the agricultural extension will be required.